Survey the antibiotic resistance of Acinetobacter baumanii and Klebsiella pneumoniae causing respiratory infections in pediatric patients at Da Nang Hospital for Women and Children (Vietnam Journal of Community Medicine, 2022)
Background: Acute respiratory infection is the disease with the highest incidence and leading cause of death in children, especially less than 5 years old. Acinetobacter baumanii and Klebsiella pneumoniae are Gram negative bacilli, which are emerging as a group of organisms that cause dangerous hosital-acquired infection globally, especially respiratory infections. Our study aimed to detect the rate of Acinetobacter baumanii and Klebsiella pneumoniae isolated from respiratory tract specimens in pediatric patients and drug resistance of these bacteria at Da Nang Hospital for Women and Chidren. Materials and methods: A descriptive cross-sectional study was conducted on 95 respiratory tract specimens from pediatric patients at Da Nang Hospital for Women and Children from November 2020 to June 2021. Bacteria strains causing respiratory infections were identified and detected antibiotic resistance by Vitek 2 compact and Kirby - Bauer method. Results: Among the 95 samples, the number isolates of Acinetobacter baumanii were 14 (14.7%); the number Klebsiella pneumoniae strains were 20 (21.1%). A. baumannii strains were mostly resistant to broad-spectrum cephalosporin antibiotics, followed by penicillin group antibiotics combined with β-lactamase inhibitors. K. pneumoniae strains were 95-100% resistant to antibiotics of the penicillin group (ampicillin), penicillin in combination with a β-lactamase inhibitor (ampicillin/sulbactam) or first-generation cephalosporin (cefazolin). There were 4 strains of A. baumannii and 8 strains of K. pneumoniae identified as multidrug-resistant, isolated mainly from the Department of Pediatric Emergency - Intensive Care - Anti-poison. Conclusions: The rate of acute respiratory infection of A. baumannii and K. pneumoniae were 14.7% and 21.1%, respectively. Multidrug-resistant strains of Acinetobacter baumanii and Klebsiella pneumoniae were mainly isolated from the Department of Pediatric Emergency - Intensive Care - Anti-poison.
Keywords: Respiratory infection, Acinetobacter baumanii, Klebsiella pneumoniae.